2014
DOI: 10.1017/jfm.2014.576
|View full text |Cite
|
Sign up to set email alerts
|

On the modulating effect of three-dimensional instabilities in open cavity flows

Abstract: Open cavity flows are known to select and enhance locked-on modes or tones. High-energy self-sustained oscillations arise within the shear layer, impinging onto the trailing edge of the cavity. These self-sustained oscillations are subject to amplitude modulations (AMs) at multiple low frequencies. However, only a few studies have addressed the identification of the lowest modulating frequencies. The present work brings to light salient AMs of the shear layer waves and identifies their source as three-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 80 publications
(121 reference statements)
2
18
0
Order By: Relevance
“…This area, which reflected the interaction of M with all other modes present in the spectrum, indicated a strong correlation between the lowest modulating frequency and all the other characteristic modes induced by shear layer fluctuations. As pointed out by Basley et al[15] this was the influence of the centrifugal instabilities along the recirculating flow inside the cavity. The fact that the IWBC indicated that the low Strouhal number interaction persisted for the whole temporal evolution of the signal is important because, even if in particular time samples the main Rossiter-Heller modes were not active, the instabilities persisted and continued to exchange energy across a wideband spectrum.…”
mentioning
confidence: 81%
“…This area, which reflected the interaction of M with all other modes present in the spectrum, indicated a strong correlation between the lowest modulating frequency and all the other characteristic modes induced by shear layer fluctuations. As pointed out by Basley et al[15] this was the influence of the centrifugal instabilities along the recirculating flow inside the cavity. The fact that the IWBC indicated that the low Strouhal number interaction persisted for the whole temporal evolution of the signal is important because, even if in particular time samples the main Rossiter-Heller modes were not active, the instabilities persisted and continued to exchange energy across a wideband spectrum.…”
mentioning
confidence: 81%
“…Despite this fact, considering their decisive impact upon the amplitude modulation of the self-sustained oscillations of the flow, as was shown in Brès & Colonius (2008), Basley et al (2014), these centrifugal instabilities can arise as the determining effects behind the disturbing consequences of cavities, for instance in transport.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been recently shown that the first instability does not occur in the shear layer but inside the cavity, as shown in Brès & Colonius (2008), Meseguer-Garrido et al (2011), Alizard, Robinet & Gloerfelt (2012). As reported in these studies, frequencies associated with the inner-flow structures are approximately two orders of magnitude smaller than the dominant (shear-layer) frequencies (see also Basley et al 2013Basley et al , 2014). Indeed, fluid particle trajectories are bent when entering the recirculating flow inside the cavity, which may lead to the development of centrifugal instabilities.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…They reported consistency between the POD modes and the vortices in the wake of the jet and argued that first few modes are typically associated with large-scale flow structures. Basley et al [21] and Podvin et al [22] also reported direct relation between the POD modes and the prominent flow structure.…”
Section: Proper Orthogonal Decomposition (Pod) Analysismentioning
confidence: 92%